Proceedings of the 3rd International Conference on Innovative Research Across Disciplines (ICIRAD 2019) 2020
DOI: 10.2991/assehr.k.200115.042
|View full text |Cite
|
Sign up to set email alerts
|

STEM Oriented Mathematics Learning with GeoGebra

Abstract: This paper presents a series of GeoGebra-based mathematical applet (mathlets) for science and math subjects, developed for elementary, middle, high school, and Calculus students. The mathlets were developed in order to fulfill requirements for qualified mathematics learning as expected by the K-13 curriculum. Almost all of the mathlets have been developed by using scientific phenomenon or real-life as their background. By doing this, it was expected that students will be more motivated in learning mathematics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This independent learning was further demonstrated and deconstructed by Suweken [14]. In that study, observations and data showed that teachers in Indonesia lack the ability to successfully impart their mathematical knowledge to their students and that they still have much room for improvement.…”
Section: Synthesis In Science and Engineering Educationmentioning
confidence: 86%
See 2 more Smart Citations
“…This independent learning was further demonstrated and deconstructed by Suweken [14]. In that study, observations and data showed that teachers in Indonesia lack the ability to successfully impart their mathematical knowledge to their students and that they still have much room for improvement.…”
Section: Synthesis In Science and Engineering Educationmentioning
confidence: 86%
“…This encourages the application of mathematics and the integration of STEM subjects through the Standards for Mathematical Practice, which can bridge the gap in STEM-related activities [14]. In the study [14], GeoGebra mathematics applets (mathlets) were given to the students, who were then allowed to explore and test them and then showcase their results. These GeoGebra mathlets allowed the students to realistically apply, practice, and enhance their skills in mathematics and STEM education.…”
Section: Synthesis In Science and Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation